The flow of peoples: international migration as a revolutionary force - Chesnais, Jean-Claude (2008)
History shows that migration usually moves from areas where population is growing fast to regions where this increase is slower. At present immigration from poor regions to richer coun tries outstrips emigration from developed countries. A century ago in Europe and now in the poorest countries migration has relieved tensions bred by declining mortality and accelerating popula tion growth. The map of international migration changes from decade to decade as each country's demographic transition matures. Although historical migration ﬂows still continue this will not lead to a demographic explosion as fertility rates have declined signiﬁcantly and aging population increases all over the world. World population is estimated to remain stagnant at around 8 thousand million before it decreases slowly through this century. Thus migration raises the challenge of a global multiethnic society.